LEADERS OF UTC- AGENCTS FOR DEVELOPING TERRITORIES IN CONDITIONS OF CHANGE - Verbovska, L.S. (The actual problems of regional economy development, 2020)
The article reveals important aspects of the quality of the regional leader in the united territorial communities. These include: the formation of a team of like-minded people, the ability to work in a team, join the team in the process of learning, carry out a constant analysis of their own experience. According to the results of the study, community development depends on the leaders of OTs, which will create conditions for a comfortable and safe stay in OTG. The important skills of team members implementing changes are considered.